2005
DOI: 10.1051/lait:2005035
|View full text |Cite
|
Sign up to set email alerts
|

Making of Kashkaval cheese from bovine micellar casein powder

Abstract: -Enrichment in micellar casein of bovine milk for making Kashkaval cheese was studied in order to face yearly variations in the composition of collected milk. Increase in casein content from 22.90 ± 0.01 g·kg -1 to 26.10 ± 0.02 g·kg -1 did not request change in the process parameters and led to cheeses with typical texture and an increase in the recovery of fat and casein in the cheese due to the acceleration of the organisation of the rennet curd matrix and a greater final firmness. The cheese yield was incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Andiç et al (2011) reported that the levels of watersoluble N, 12% trichloroacetic acid-soluble N, and 5% phosphotungstic acid-soluble N increased significantly in Kashkar (Turkish equivalent of Kashkaval) over a 180-d ripening period at 4°C to an extent depending on whether cheese was vacuum packaged or not. Simov et al (2005) studied the effect of increasing milk casein content from 2.29 to 2.6% with micellar casein on Kashkaval cheese; fortification increased the percentage of milk fat and protein recovered to cheese and cheese yield, while giving cheese with typical texture. El-Safti and Khalil (2012) reported that the production of good-quality Trappist from water-buffalo milk necessitated the addition of ~0.1 to 0.15% sodium citrate to the cheese milk, readjustment of the milk pH to original value by addition of 5% lactic acid solution, and the use of Lactobacillus helveticus as an adjunct culture.…”
Section: Introductionmentioning
confidence: 99%
“…Andiç et al (2011) reported that the levels of watersoluble N, 12% trichloroacetic acid-soluble N, and 5% phosphotungstic acid-soluble N increased significantly in Kashkar (Turkish equivalent of Kashkaval) over a 180-d ripening period at 4°C to an extent depending on whether cheese was vacuum packaged or not. Simov et al (2005) studied the effect of increasing milk casein content from 2.29 to 2.6% with micellar casein on Kashkaval cheese; fortification increased the percentage of milk fat and protein recovered to cheese and cheese yield, while giving cheese with typical texture. El-Safti and Khalil (2012) reported that the production of good-quality Trappist from water-buffalo milk necessitated the addition of ~0.1 to 0.15% sodium citrate to the cheese milk, readjustment of the milk pH to original value by addition of 5% lactic acid solution, and the use of Lactobacillus helveticus as an adjunct culture.…”
Section: Introductionmentioning
confidence: 99%
“…These studies were further evaluated for eligibility. Seven studies were found to be eligible for inclusion in this review (Table 1),[7-13]and 4 studies were excluded [20-23]. The quality of studies were good with Jadad score varying from 3 to 5.…”
Section: Resultsmentioning
confidence: 99%
“…Data from 5 studies including 372 patients were used for this analysis [9-13]. Overall there was no significant change in blood or immunologic parameters in the probiotic group, SMD -0.10 (95% CI -0.26, 0.06; P = 0.22).…”
Section: Resultsmentioning
confidence: 99%
“…Increase in casein content from 22.90 g/kg to 26.10 g/kg led to cheeses with typical texture and an increase in the recovery of fat and casein by 2.5 and 3.5% respectively; cheese yield increased by about 17%. The resultant cheese had greater firmness too [47].…”
Section: Application Of Micellar Caseinmentioning
confidence: 99%